Effect of Zinc and Nitric Oxide on Monocyte Adhesion to Endothelial Cells under Shear Stress - Lee, Sungmun (2011)
This study describes the effect of zinc on monocyte adhesion to endothelial cells under different shear stress regimens, which may trigger atherogenesis. Human umbilical vein endothelial cells were exposed to steady shear stress (15 dynes/cm(2) or 1 dyne/cm(2)) or reversing shear stress (time average 1 dyne/cm(2)) for 24 hours. In all shear stress regimes, zinc deficiency enhanced THP-1 cell adhesion, while heparinase III reduced monocyte adhesion following reversing shear stress exposure. Unlike other shear stress regimes, reversing shear stress alone enhanced monocyte adhesion, which may be associated with increased H(2)O(2) and superoxide together with relatively low levels of nitric oxide (NO) production. L-N(G)-Nitroarginine methyl ester (L-NAME) treatment increased monocyte adhesion under 15 dynes/cm(2) and under reversing shear stress. After reversing shear stress monocyte adhesion dramatically increased with heparinase III treatment followed by a zinc scavenger. Static culture experiments supported the reduction of monocyte adhesion by zinc following endothelial cell cytokine activation. These results suggest that endothelial cell zinc levels are important for the inhibition of monocyte adhesion to endothelial cells, and may be one of the key factors in the early stages of atherogenesis.